Recent Trends in Stratospheric Chlorine From Very Short‐Lived Substances. Issue 4 (16th February 2019) - Hossaini, Ryan; Atlas, Elliot; Dhomse, Sandip S.; Chipperfield, Martyn P.; Bernath, Peter F.; Fernando, Anton M.; Mühle, Jens; Leeson, Amber A.; Montzka, Stephen A.; Feng, Wuhu; Harrison, Jeremy J.; Krummel, Paul; et al.
Abstract: Very short‐lived substances (VSLS), including dichloromethane (CH2 Cl2 ), chloroform (CHCl3 ), perchloroethylene (C2 Cl4 ), and 1, 2‐dichloroethane (C2 H4 Cl2 ), are a stratospheric chlorine source and therefore contribute to ozone depletion. We quantify stratospheric chlorine trends from these VSLS (VSLCltot ) using a chemical transport model and atmospheric measurements, including novel high‐altitude aircraft data from the NASA VIRGAS (2015) and POSIDON (2016) missions. We estimate VSLCltot increased from 69 (±14) parts per trillion (ppt) Cl in 2000 to 111 (±22) ppt Cl in 2017, with >80% delivered to the stratosphere through source gas injection, and the remainder from product gases. The modeled evolution of chlorine source gas injection agrees well with historical aircraft data, which corroborate reported surface CH2 Cl2 increases since the mid‐2000s. The relative contribution of VSLS to total stratospheric chlorine increased from ~2% in 2000 to ~3.4% in 2017, reflecting both VSLS growth and decreases in long‐lived halocarbons. We derive a mean VSLCltot growth rate of 3.8 (±0.3) ppt Cl/year between 2004 and 2017, though year‐to‐year growth rates are variable and were small or negative in the period 2015–2017. Whether this is a transient effect, or longer‐term stabilization, requires monitoring. In the upper stratosphere, the modeled rate of HCl decline (2004–2017) is −5.2% per decade with VSLS included, in good agreement to ACE satellite data (−4.8% per decade), and 15% slower than a model simulation without VSLS. Thus, VSLS have offset a portion of stratospheric chlorine reductions since the mid‐2000s. Plain Language Summary: It is well established that long‐lived halogen‐containing compounds of anthropogenic origin, such as chlorofluorocarbons, have led to depletion of the stratospheric ozone layer. As production of these compounds is now controlled by the Montreal Protocol, the atmospheric abundance of chlorine/bromine is in decline, and the ozone layer should "recover" in coming decades. Here we consider the contribution of Very Short‐Lived Substances to stratospheric chlorine. These compounds also have anthropogenic sources, though are much less efficient at destroying ozone compared to, for example, most chlorofluorocarbons (per molecule emitted) as they break down more readily close to Earth's surface. Using surface observations and atmospheric model simulations, we show that stratospheric chlorine from short‐lived substances has increased since the early 2000s. This increase is also apparent from airborne measurements of their atmospheric abundance over the same period. Using the model in conjunction with satellite estimates of stratospheric chlorine, we show rising levels of short‐lived substances may be causing upper stratospheric chlorine to decline at a slower rate relative to what would be expected in their absence. While this offset in the rate of chlorine decline is modest (15%), it is nonnegligible and should be considered in the analysis of stratospheric composition trends. Key Points: Stratospheric chlorine from very short‐lived substances increased by 3.8 ppt/year over 2004–2017, with a growth slowdown in 2015–2017 Chlorine from short‐lived substances improves model representation of upper stratospheric HCl trends Short‐lived chlorine offsets the 2004–2017 rate of upper stratospheric HCl decline by 15%